Ecological stoichiometry between leaves, litter and soil of dominant species in the forest community of rock-stream periglacial landforms in Mt. Laotudingzi - Lan Wang; Daqi Liu (PLoS ONE, 2025)
This study investigates the ecological stoichiometric characteristics of carbon (C), nitrogen (N), and phosphorus (P) across the leaf-litter-soil continuum in the block stream forest community of Laotudingzi Mountain, a representative paleo-periglacial landform in northeastern China. Utilizing X-ray fluorescence spectroscopy (XRF), we analyzed 13 dominant tree species (10 broadleaf, 3 coniferous) to unravel nutrient limitation mechanisms and cross-media coupling in this oligotrophic cryogenic ecosystem. Results indicate that P is the primary limiting nutrient, with mean N: P ratios in leaves (12.84), litter (11.25), and soil (8.05) below the global threshold for P limitation (N: P < 14). Cross-media stoichiometric feedbacks reveal efficient P cycling: leaf N: P ratios show significant positive correlations with litter P content (R = 0.557, P < 0.05) and negative correlations with litter C: P ratios (R = −0.581, P < 0.05), while synchronized P dynamics between litter and soil (R = 0.538, P < 0.1) underscore litter decomposition as the primary driver of soil P replenishment. Adaptive nutrient strategies emerge through stoichiometric plasticity, where accelerated P mineralization via low C: P ratios (342.88) compensates for C-N cycling inefficiencies despite inhibitory litter C: N ratios (32.3). These findings highlight the biogeochemical resilience of periglacial forests and provide critical insights for mitigating P limitation, guiding species selection in restoration, and optimizing litter management to enhance ecosystem stability under climate change.